Poleward eddy-induced warm water transport across a shelf break off Totten Ice Shelf, East Antarctica - Hirano, Daisuke; Mizobata, Kohei; 溝端, 浩平; ミゾバタ, コウヘイ; Sasaki, Hiroko; Murase, Hiroto; Tamura, Takeshi; Aoki, Shigeru (Communications Earth & Environment, 2021)
Ice mass loss in the Wilkes Land sector of East Antarctica and the Amundsen and Bellingshausen Sea sectors of West Antarctica has contributed to a rise in sea levels over several decades. The massive continental ice behind the Totten Ice Shelf, equivalent to a few meters of sea-level rise, is grounded well below sea level and therefore, potentially vulnerable to oceanic heat. Here, we present analyses of comprehensive hydrographic observations at the continental slope and shelf break regions off Totten Ice Shelf. We provide robust evidence that the relatively warm Circumpolar Deep Water that originates at intermediate depths in the Antarctic Circumpolar Current is transported efficiently towards the shelf break by multiple cyclonic eddies. We propose that these semi-permanent cyclonic circulations play a critical role in transporting the available ocean heat towards Totten Ice Shelf, and melting it from underneath, thus eventually influencing the global climate. 20H04970 journal article